1910. (21st April 2016) - Unknown
Abstract : Adopted with much enthusiasm by the Liberal '300' at Droitwich. In the evening to a packed and rollicking meeting at Kidderminster. Sir Edward Fraser, Liberal candidate for the Borough and Mr. Brooks, our working-man humourist and orator of Stourbridge, also addressed meeting.